2018
DOI: 10.1097/bsd.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cervical Decompression Surgery on Gait in Adult Cervical Spondylotic Myelopathy Patients

Abstract: Study Design: This is a prospective cohort study. Objective: To evaluate the effect of cervical decompression surgery on the biomechanics of the spine and lower extremities in cervical spondylotic myelopathy (CSM) patients and compare with asymptomatic controls. Summary of Background Data: Difficulties with balance and gait are one of the most common manifestations of CSM. Patients with CSM have a slower gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…Thus far, only four studies have investigated the decompressed state of CSM in animal models (Harkey et al, 1995;Karadimas et al, 2015b;Dhillon et al, 2016;Haddas et al, 2018). Harkey et al (1995) demonstrated that decompression can improve neurological function and can alter the necrosis and cavitation of spinal cord tissue in a dog model.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, only four studies have investigated the decompressed state of CSM in animal models (Harkey et al, 1995;Karadimas et al, 2015b;Dhillon et al, 2016;Haddas et al, 2018). Harkey et al (1995) demonstrated that decompression can improve neurological function and can alter the necrosis and cavitation of spinal cord tissue in a dog model.…”
Section: Introductionmentioning
confidence: 99%
“…Longer duration of disease has also been identified to be a poor prognostic factor for recovery. [222728293031] The duration of symptoms in our patients ranged from 15 days to 20 years (average 16 months). Despite this long duration of symptoms, the clinical outcome was uniformly satisfactory.…”
Section: Discussionmentioning
confidence: 97%
“…Disturbed gait of cervical myelopathy patients has been reported in the literature, characterized by a slower walking speed, shorter step length, longer step time, reduced range of joint motions (62)(63)(64), and altered timing and duration of muscle activities (65). After surgery for cervical decompression, improvement is observed in walking speed, step time, step length, and joint motions (66)(67)(68) and in knee kinetics (69). While the existing studies dealt with cervical myelopathy patients who could ambulate autonomously before and after surgery, in this study, we dealt with a thoracic myelopathy patient who had difficulty walking before and after surgery.…”
Section: Discussionmentioning
confidence: 99%